(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
Pain has always been a distressing feeling or the unpleasant sensory and emotional experience. A pain free life is longing of everyone and this is the biggest challenge for the medical science practitioners nowadays as how to provide efficient pain management. In modern medicine we have variety of pain-relieving medications that works brilliantly for short period of time and when used for longer duration they come up with various side effects. So there is a need to find a way to relieve pain without much suffering to the patient and Agnikarma is one of the sound ways to do so. It is therapeutic burning with special tools on specific sites according to the disease. It is a parasurgical procedure that is utilized as curative procedure, or as postoperative procedure or in hemostatic manner. Agnikarma is derived from Ayurveda, a renowned Indian system of medicine, which is procedure used generally for the management of pain and also for curing various disorders. In Ayurveda Vata Dosha is responsible mainly for various types of Ruja or pain in the body and Agnikarma is one of the best method to pacifying Vata and Kapha Dosha and hence relieves pain. Acharya Sushruta, a renowned Vedic Indian surgeon has very well explained the eminence of Agnikarma by saying that the recurrence of disease will not be there if once they are treated with Agnikarma. He in his text mentioned various Dravyas according to the diseases through which Agnikarma can be performed. Also several Dahanaupkarana are mentioned in the classics that provide practitioner abundant methods to perform Agnikarma without much limitations